Performance of soil test crop response on productivity and profitability of rice (Oryza sativa) in inceptisols of raigarh district of chhattisgarh plains - Singh, S.P.; Paikra, K.K.; Patel, Chanchala Rani (Annals of Agricultural Research, 2019)
Field experiments were carried out on rice (Oryza sativa) during kharif 2016 to study the performance of soil test crop response on productivity and profitability of rice (Oryza sativa) in Inceptisols of Raigarh district of Chhattisgarh plains. The fertilizer adjustment equations are derived by the All India Coordinated Research Project (AICRP), College of Agriculture, IGKV, Raipur (C.G.). The results revealed that targeted yield of rice (45 and 50 q ha–1) have been achieved by using the plant nutrients on the basis of targeted yield concept (soil test crop response). The N, P and K fertilizers were contributed in increase yield 46.66 and 47.90 q ha–1 in first location, 47.50 and 49.10 q ha–1 in second location, 48.10 and 49.50 q ha–1 in third location and 48.30 and 51.75 q ha–1 in fourth location as compared to farmers practice which were 30.75, 32.60, 31.75 and 33.45 q ha–1, respectively. The maximum net returns of rice first location (Rs. 32216.30 and Rs. 33834.50), second location (Rs. 32072.50 and Rs. 34160.50), third location (Rs. 33630.50 and Rs. 35457.50) and fourth location (Rs. 31799.00 and Rs. 36301.25) were obtained in treatment where plant nutrients applied as per soil test value (STCR treatment). The nutrient requirement (NR) contribution of nutrients from soil (CS), fertilizer (CF) and farm yard manure (CFYM) were evaluated the data on soil test values, fertilizer nutrients doses, nutrient uptake and rice yield. Soil test based fertilizer adjustment equations for targeted yield of rice crop 1.53 kg N, 0.33 kg P and 2.08 kg K were required to produce one quintal of rice grain yield. The per cent contribution from soil was recorded as 18.13 for N, 61.40 for P and 20.94 for K in case of rice crop. The per cent contribution of organic source (FYM) for N, P and K were recorded 6.95, 3.35 and 2.92 and 3.47, 5.45 and 2.13 for rice. The results clearly indicates that soil test based fertilizers adjustment equations were evolved for rice crop to achieve a definite yield target. Ready reckoners chart for fertilizer N, P2O5 and K2O application based on the soil test values for specific yield targets of rice and wheat were also prepared which are useful for the soil testing laboratories. Therefore, obtaining maximum gain, sustain soil fertility, health status and application of plant nutrients as per soil test value (STCR) is essential.